A Systematic Literature Review on Emotional Text for Malay Corpus - Muhd Adnan, Hafizuddin Muhd; Yaacob, Hamwira; Awang Abu Bakar, Normi Sham (International Journal on Perceptive and Cognitive Computing, 2021)
The existence of corpus, especially online corpus, fabricates benefits not only to the linguistic area, but also benefits to others, for instance to academicians especially researchers. Research trends on corpus shows that study is done to upgrade the performance and functionality, for example toward the emotional corpus. These emotional corpora been used widely not only by researcher in linguistic but also by psychologist, the legal firm and also by stakeholder by referring to the emotional annotation in the corpus to understand about their client emotion and behavior. However, the study on the Malay emotional corpus is still left behind where currently there is no available study or paper been published regarding on Malay emotional corpus and also no development method yet been study on Malay Emotional Corpus. Therefore, this paper aims to focus on applying the systematic literature review (SLR) regarding the emotional corpus. The objective of this study is to understand and identify the available technique and methods that have been used in developing the emotional corpus based on text. The methodology used in this paper is by applying a systematic approach known as the Preferred Reporting Items for Systematic reviews and Meta- Analyses (PRISMA). The articles that have been reviewed through SLR are obtained from the Scopus online database. Articles are selected based on the time range between years 2011 until years 2020.These articles are reviewed and analyzed through four PRISMA approaches which is the Identification, Screening, Eligibility and Included approach. After going through the process, this paper managed to get 35 articles for the purpose of SLR for detail reviewed. Initiating SLR in this study, several components or areas are identified for the reviewing purpose. This paper review regarding the method applied, the domain or application, modality, name of the corpus involved, the label of corpus (language) and then what is the measurement based they used in the methodology in their study. At the end of the study, this paper significantly brought a summary in helping to understand the available method and technique used for emotion recognition based on text for the purpose of emotional Corpus development hence identifying the most applicable method used. This bring as a source based for the future works in developing Malay emotional Corpus.